IMPACT OF THE LOSS AND THEFT OF ELECTRONIC DATA ON COMPANIES - Stefan IOVAN; Marius Bogdan DINU (Fiabilitate şi Durabilitate)
Crimes committed via the Internet are no longer a novelty either for authorities and companies or for the general public, including potential victims. Transshipment of the human being to the virtual environment has not left out the bad habits and the propensity to steal of some people. On the contrary, it seems that the unprecedented development of the information technology [1] has given birth to a new category of dangerous criminals - those who steal by means of a computer not just huge amounts of money, but also ideas, data, identities and information from the most varied and unexpected areas. According to IT jargon, thefts via IT are those illegal activities by which the criminal(s) causes (cause) losses to those who store in the online environment personal information, saleable information, money or other valuables. Another “booming” category of Internet crime is the theft of identity. This is a serious crime that most often than not is targeted to stealing money. In today's society, we are often requested to disclose a great deal of personal information about who we are and what we do, such as our signature, address, passwords, phone numbers, and in particular information about our credit cards and the various banking services we use. The problem concerns not only the theft of data and information, but also the loss of data and information. This paper aims to tackle a few important aspects of this issue.